Efeitos sedativos e cardiorrespiratórios da detomidina com ou sem diazepam em eqüinos submetidos ao procedimento odontológico - Marina Lopes Castro (2019)
The use of the combination of alpha 2 agonists and benzodiazepines in the equine species (Equus ferus) should be better evaluated, mainly through clinical studies, with an approach to the advantages and disadvantages of their use in seasonal maintenance procedures such as procedures for example, in order to guarantee a lower risk of nerve compression, lower anesthetic risk and lower hemodynamic depression, all of which are potentiated in decubitus animals. The objective of this study was to evaluate and compare sedative effects, clinical parameters, as well as the quality of relaxation, degree of movement and language exposure using detomidine with or without diazepam administered intravenously in horses. Twelve adult horses (7.15 ± 6.74 years), with no defined breed and different sexes, with a mean weight of 286 ± 56 kg, submitted to correction of dental arches. The animals were randomly allocated into two groups (n = 6), Group 1-DD (detomidine 20 g.kg-1 and diazepam 0.02 mg.kg-1) and Group 2-DS (detomidine 20 g.kg- 1 and NaCl 0.9% 0.004 ml.kg -1). Cardiac parameters (systolic blood pressure - SBP, heart rate - HR), and electrocardiogram respectively, presentce of arrhythmias, and respiratory (respiratory rate - f) were evaluated. Rectal temperature, chin-soil distance, degree of tongue relaxation, quality of relaxation and tongue exposure in centimeters, and degree of ataxia were assessed by means of muscle relaxation scores of the tongue and movement of the head and ataxia, respectively. All parameters were measured before the pre-anesthetic medication (baseline) and until the end of the dental procedure (8 moments). The variables of anesthesia evaluation were described by measures of central tendency. For all analyzes the significance level of 5% was considered. There was no statistical difference between the DD and DS groups. However, there are evaluated time effect on heart rate, respiratory rate, blood pressure, PR interval, chin distance, and lingual relaxation, always with a difference in relation to baseline. The distance chin soil as well as the degree of the surgeon presented smaller distances in relation to the soil and better relaxation, respectively, always with respect to the basal moment. It was concluded that both protocols caused adequate sedation. However, there is no need to use diazepam in the dose and methodology used in this study. Further research with different doses of diazepam is necessary to verify the effect of this on the relaxation and lingual movement.